2019
DOI: 10.3390/cancers11070993
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Proton Beam Therapy for Esophageal Cancer: Multicenter Retrospective Study in Japan

Abstract: There are few reports about the clinical results of proton beam therapy for esophageal cancer in a large population. The purpose of this study was to evaluate the clinical results of proton beam therapy for esophageal cancer in a large population using a multicentered database. Between January 2009 and December 2013, patients newly diagnosed with esophageal cancer and who had received proton beam therapy were retrospectively recruited from a database of four proton beam therapy centers in Japan. Two hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…The 5-year rates of overall survival (OS) and local control of patients with stages I and II were 75.4% and 74.0%, respectively, and the corresponding rates of stages III and IV were 36.8% and 53.8%, respectively. Furthermore, grade 3 cardiopulmonary toxicities were observed in only three (1.5%) patients [ 38 ]. Table 1 shows that the incidence of cardiopulmonary toxicities in CCRT for esophageal cancer after PBT was less than that after photon RT [ 39 , 40 , 41 , 42 , 43 ].…”
Section: The Role Of Particle Beam Therapy In Multidisciplinary Treatments In Clinicsmentioning
confidence: 99%
“…The 5-year rates of overall survival (OS) and local control of patients with stages I and II were 75.4% and 74.0%, respectively, and the corresponding rates of stages III and IV were 36.8% and 53.8%, respectively. Furthermore, grade 3 cardiopulmonary toxicities were observed in only three (1.5%) patients [ 38 ]. Table 1 shows that the incidence of cardiopulmonary toxicities in CCRT for esophageal cancer after PBT was less than that after photon RT [ 39 , 40 , 41 , 42 , 43 ].…”
Section: The Role Of Particle Beam Therapy In Multidisciplinary Treatments In Clinicsmentioning
confidence: 99%
“…To our knowledge, the failure of RTOG 94-05 was related to high rates of toxicities in 2D era. A latest study in Japan used proton beam therapy for esophageal cancer and reported lower rates of toxicities in comparison to photon radiotherapy [38] . The biological effective dose (BED) in this study was up to 87.2 Gy (67.2 -96.1 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…Ono et al reported the results of multicenter retrospective study in Japan with 202 (including 90 inoperable) esophageal cancer patients. 85 The 3-year and 5-year OS was 66.7 and 56.3%, respectively. The 5-year LRC was 64.4%.…”
Section: Biology Of Proton Beam Therapymentioning
confidence: 92%